Potential sources of nitrogen in an ant-garden tank-bromeliad - Leroy, Céline (Landes Bioscience, 2009)
Epiphytic plants in general and bromeliads in particular live in a water and nutrient-stressed environment often limited in nitrogen. Thus, these plants have developed different ways to survive in such an environment. We focused on Aechmea mertensii (Bromeliaceae), which is both a tank-bromeliad and an ant-garden (AG) epiphyte initiated by either the ants Camponotus femoratus or Pachycondyla goeldii. By combining a study of plant morphology and physiology associated with aquatic insect biology, we demonstrate that the ant species influences the leaf structure of the bromeliad, the structure of the aquatic community in its tank, and nutrient assimilation by the leaves. Based on nitrogen and nitrogen stable isotope measurements of the A. mertensii leaves, the leaf litter inside of the tank and the root-embedded carton nest, we discuss the potential sources of available nitrogen for the plant based on the ant partner. We demonstrate the existence of a complex ant-plant interaction that subsequently affects the biodiversity of a broader range of organisms that are themselves likely to influence nutrient assimilation by the A. mertensii leaves in a kind of plant-invertebrate-plant feedback loop.